KEPRIBADIAN BIG FIVE PERSONALITY DAN EFIKASI GURU DI SEKOLAH DASAR DENGAN KURIKULUM 2013 - FITRI LESTARI ISSOM; TRI PURNAMA SARI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2016)
The purpose of this study is to determine the effect between Big Five Personality (openness to experience, conscientiousness, extraversion, agreeableness, neuroticism) to teacher efficacy in elementary school with curriculum 2013. The design of this this study is a quantitative method. The measuring instrument used Big Five Inventory and Teacher Sense of Efficacy Scale that has been adapted into the Indonesian language. The number of samples in this study are 91 elementary school teachers who teach using curriculum 2013 in Bekasi City. The results of the research based on linear regression analysis showed a significant effects between Big Five Personality type of openness to experience, conscientiousness, extraversion, and neuroticism to the teacher efficacy in elementary school with curriculum 2013. The results show that extraversion has the higher effect on teacher efficacy which is 24.1% with a positive effect on teacher efficacy.